2010
DOI: 10.1111/j.1465-3362.2009.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Is point of access to needles and syringes related to needle sharing? Comparing data collected from pharmacies and needle and syringe programs in south‐east Sydney

Abstract: The high prevalence of receptive equipment sharing among pharmacy clients indicates a need to improve access to needles and syringes and ancillary equipment, possibly by including ancillary equipment at no cost in existing pre-packaged pharmacy products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…Also, our sample was recruited from pharmacies as part of a larger study that was conducted for a different purpose. We know from previous research that pharmacyrecruited respondents more commonly engage in syringe sharing than respondents recruited from other venues such as NSP [22,23]. Future research examining syringe coverage among Australian PWID should sample from a broader range of syringe distribution venues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, our sample was recruited from pharmacies as part of a larger study that was conducted for a different purpose. We know from previous research that pharmacyrecruited respondents more commonly engage in syringe sharing than respondents recruited from other venues such as NSP [22,23]. Future research examining syringe coverage among Australian PWID should sample from a broader range of syringe distribution venues.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, studies that use Bluthenthal's measure of syringe coverage have based their calculations on syringes obtained from needle and syringe programs (NSP). There is evidence to show that PWID obtain their sterile equipment from multiple sources such as pharmacies [22][23][24] and peers [25][26][27], and some researchers have identified the need for syringe coverage indicators to include these in their calculations [28].…”
Section: Introductionmentioning
confidence: 99%
“…33 In addition, Australian research comparing IDUs surveyed at NSPs with those surveyed at pharmacies found that most IDUs used both venues to obtain needles and syringes; only a small proportion (17%) reported exclusive use of pharmacies. 34 …”
Section: Limitationsmentioning
confidence: 99%
“…Pharmacy-recruited participants are an ideal comparison group as it has been previously reported that exclusive pharmacy users are more likely to engage in BBV-related risk behaviours when compared to exclusive users of needle and syringe programs [21]. PWID who use pharmacies are thus a group of interest that should be captured by behavioural surveillance sampling methods.…”
Section: Introductionmentioning
confidence: 99%